PERAN BUDAYA TRADISIONAL BALI UNTUK DUNIA DALAM PRESIDENSI G20 INDONESIA - Yusmini, Ni Made; Sumariana, I Gede Ari (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
This research was conducted with the aim of finding out the role of Balinese culture, strategy and impact on improving human resources for craftsmen in Tenganan Pegringsingan Village. The data analysis technique used is a non-statistical analysis technique because the data in this research is qualitative data which prioritizes descriptions and arguments from researchers and sources. The results of the research state that Balinese culture, especially gringsing woven cloth, has an important role for the world, namely being a cultural asset and can be used as a means of improving the regional economy. Balinese culture, especially gringsing woven cloth, has a big impact on improving human resources for gringsing woven cloth craftsmen. Based on this research, it is necessary to preserve culture, increase human resources and utilize large events such as the G20 Presidency. In order to be able to provide reference contributions in the field of management economics and be able to provide suggestions and criticism to Gringsing woven fabric entrepreneurs to always maintain and improve product quality.